Kyrgyz Republic : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
The attached Joint Staff Assessment (JSA) of the Poverty Reduction Strategy Paper Progress Report on the Kyrgyz Republic highlights the poverty diagnosis and macroeconomic framework. Poverty developments have been particularly encouraging in the rural areas, where the majority of Kyrgyzstan's poor live, with a relatively larger reduction in the poverty level, and reductions in extreme poverty and expenditure inequality. The IMF staff welcomes the work initiated to improve costing and prioritization and poverty analysis.